Pengaruh Implementasi Sistem Informasi Akuntansi dan Sistem Pengendalian Internal terhadap Kinerja Karyawan Koperasi Unit Desa : (Studi Kasus Desa Karya Mukti) - Yepita Ghufiromah Yani (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to examine the influence of the implementation of Accounting Information Systems (AIS) and Internal Control Systems (ICS) on employee performance at the Village Unit Cooperative (KUD) in Karya Mukti Village, Mesuji District, Ogan Komering Ilir Regency, South Sumatra. KUD plays a crucial role in improving the economic welfare of rural communities but often faces challenges in financial management and employee performance enhancement. The research methods used include descriptive testing, validity and reliability testing, classical assumption testing (normality, multicollinearity, and heteroscedasticity), and multiple linear regression analysis. The results indicate that the implementation of AIS does not have a significant effect on employee performance (t-count = 0.618 < t-table = 2.018), while the implementation of ICS has a significant effect (t-count = 2.288 > t-table = 2.018). The F-test shows that both independent variables significantly affect employee performance simultaneously (p-value = 0.001 < 0.05; F-count = 7.768 > F-table = 3.22). This research is expected to provide practical contributions to the financial management of KUD and serve as a reference for policymakers in optimizing information systems and internal controls to enhance the efficiency and effectiveness of cooperative operations.